2011 Atlanta Conference on Science and Innovation Policy 2011
DOI: 10.1109/acsip.2011.6064466
|View full text |Cite
|
Sign up to set email alerts
|

Organization theory and new ways of working in science

Abstract: Dramatic changes in the practice of science over the past half a century, including trends towards working in teams and on large projects, and geographically distributed and interdisciplinary collaboration, have created opportunities and challenges for scientists. We argue that these changes in science represent new organizational forms and ways of working that also create opportunities and challenges for organization theory.We describe how applying organization theory to science can push our knowledge of rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…A cluster analysis of scientific collaborations in physics by Chompalov et al ( 4 ) revealed that the variety of organizational formats of collaborative projects range from formal and bureaucratic to informal and participatory. Recent studies show that scientific collaboration across disciplines and institutions is growing ( 5 , 6 ). However, most studies of scientific teams analyze either observed interactions between team members or products of teamwork, especially publications.…”
Section: Introductionmentioning
confidence: 99%
“…A cluster analysis of scientific collaborations in physics by Chompalov et al ( 4 ) revealed that the variety of organizational formats of collaborative projects range from formal and bureaucratic to informal and participatory. Recent studies show that scientific collaboration across disciplines and institutions is growing ( 5 , 6 ). However, most studies of scientific teams analyze either observed interactions between team members or products of teamwork, especially publications.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the processes of interdisciplinary research collaboration and methods that would encourage and support interdisciplinary research teamwork in higher education institutions are not well understood (Falk-Krzesinski et al, 2011). As Cummings and Kiesler (2011) observed, "little is known about how (and if) universities create values, procedures, and structures wherein interdisciplinary science is central" (p. 3). This study aimed to address this gap and asked the following research question:…”
mentioning
confidence: 99%